THE NEAR FUTURE OF THE OIL AND GAS INDUSTRY IS – THE YOUTH - Kochkarov Ulugbek Kabuljanovich (International Engineering Journal For Research & Development, 2021)
Although the oil and gas industry has provided a century of economic growth, in the process, the planet’s climate was severely damaged, which in turn left the oil and gas industry under constant criticism and threat. Before solving the problem, it is necessary to pay attention to it. It is safe to say that youth and innovation are the future of the oil industry. The world is paying great attention to unprecedented rapid change, rapid technological development, high competition and protection of the natural environment. The factors that determine efficiency and success are increasingly embracing change, active thinking, and the pursuit of progress. All of these qualities are inherent in young professionals. And their energy and passion are especially important for the future of the oil industry right now. It is no secret that it is often very difficult for young professionals to take a worthy place in organizations, to understand and hear them. Even if they have the qualities, knowledge and motivation that the field needs objectively.